Hidden 'pit'falls in deciphering the gonadotropin releasing hormone neuroendocrine cell lineage. (22nd September 2021) - Shan, Yufei; Wray, Susan
Abstract: To this day, the identity of gonadotropin‐releasing hormone (GnRH) progenitors remains unclear. However, the visualization of different developmental markers in subsets of GnRH neurons during early embryonic stages raised the possibility of at least two GnRH subpopulations. This observation led directly to a second question. Does visualization of different developmental markers in subsets of GnRH neurons reflect functional heterogeneity? This question remains unanswered, but as we learn more about the GnRH system, functional GnRH subpopulations become critically important to understanding GnRH function. This review addresses the development of the neuroendocrine GnRH system, specifically the heterogeneity of the GnRH neuroendocrine population. Abstract : Two subpopulations of mouse gonadotropin‐releasing hormone (GnRH) neurons are delineated by markers for Wnt1 and Islet‐1/2. (A‐C) E11.5 mouse sections. Although the majority of GnRH neurons express Islet‐1/2 (asterisk, B, red C), GnRH neurons negative for Islet‐1/2 (white arrow, B, upper box C) are also detected (A schematic of E11.5. Blue dashed box in (A) shows location of high magnification image (B). Red solid box in (A) shows the location of the high magnification in (C). (C) Triple immunostaining of sections from a E11.5 Wnt1CreRosa YFP mouse stained for GnRH (white), green fluorescent protein (GFP, green) and Islet‐1/2 (red) indicates GnRH/GFP positive cells are islet‐1/2 negative (C, dashed box and higher magnification upper panel). By contrast, GnRH cells that are GFP negative are islet‐1/2 positive (C, solid box and arrowheads, and higher magnification lower panel). (D, E) Preliminary data from adult NIH Swiss mice (>PN45) sections. (D) Immunostained for GnRH (blue) and Islet‐1/2 (brown) using standard ABC peroxidase procedures. Left panel, low magnification at the level of organum vasculosum lamina terminalis (schematic inset); Right panel, higher magnification of area boxed in (D). GnRH neurons positive for Islet‐1/2 (black arrows); and GnRH cells negative for Islet‐1/2 (white arrows) are shown. E, Fluorescence image from a brain section from an adult Wnt1Cre/RYFP mouse showing that GnRH/GFP positive neurons (dashed boxed and upper right panel) and GnRH/GFP negative neurons (solid box and lower panel) are still detected.